How Strigolactone Shapes Shoot Architecture - Khuvung, Khopeno; Silva Gutierrez, Federico A. O.; Reinhardt, Didier (Frontiers in Plant Science, 2022)
Despite its central role in the control of plant architecture, strigolactone has been recognized as a phytohormone only fifteen years ago. Together with auxin, it regulates shoot branching in response to genetically encoded programs, as well as environmental cues. A central determinant of shoot architecture is apical dominance, i.e. the tendency of the main shoot apex to inhibit the outgrowth of axillary buds. Hence, the execution of apical dominance requires long-distance communication between the shoot apex and all axillary meristems. While the role of strigolactone and auxin in apical dominance appears to be conserved among flowering plants, the mechanisms involved in bud activation may be more divergent, and include not only hormonal pathway but also sugar signaling. Here, we discuss how spatial aspects of SL biosynthesis, transport, and sensing may relate to apical dominance, and we consider the mechanisms acting locally in axillary buds during dormancy and bud activation.